Cpn60 is exclusively localized into mitochondria of rat liver and embryonic Drosophila cells. - San Martin, C.; Flores, A.I.; Cuezva, J.M. (Journal of Cellular Biochemistry, 1995)
Several reports have claimed that the mitochondrial chaperonin cpn60, or a close homolog, is also present in some other subcellular compartments of the eukaryotic cell. Immunoelectron microscopy studies, using a polyclonal serum against cpn60, revealed that the protein is exclusively localized within the mitochondria of rat liver and embryonic Drosophila cells (SL2). Furthermore, no cpn60 immunoreactive material could be found within the nucleus of SL2 cells subjected to a 1 h 37 degrees C heat-shock treatment. In contrast to these findings, immunoelectron microscopy studies, using a cpn60 monoclonal antibody, revealed mitochondrial and extramitochondrial (plasma membrane, nucleus) immunoreactive material in rat liver cells. Surprisingly, the monoclonal antibody also reacted with fixed proteins of the mature red blood cell. The monoclonal antibody, as well as cpn60 polyclonal sera, only recognize mitochondrial cpn60 in Western blots of liver proteins. Furthermore, none of the cpn60 antibodies used in this study recognized blotted proteins from rat red blood cells. Therefore, we suggest that the reported extramitochondrial localization of cpn60 in metazoan cells may be due to cross-reactivity of some of cpn60 antibodies with conformational epitopes also present in distantly related cpn60 protein homologs that are preserved during fixation procedures of the cells.